Niger : Poverty Reduction Strategy Paper Progress Report. (IMF Staff Country Reports; Country Report ;, 2003)
In the social sectors, encouraging results were obtained in education. The Ten-Year Education Program was finalized, creating a solid basis for the implementation of actions in this sector. According to the most recent estimates, the basic enrolment rate was 41.7 percent in 2002 compared with 37.3 percent in 2001. These results are owing to the efforts of the government in recruiting volunteer teachers and building and equipping of classrooms. The government also adopted a national policy for higher education.